Sustainability reporting and greenwashing: Implications for transparency and firm value: A systematic literature review - Sevia Dian Saraswati; Ferry Irawan; Anda Dwiharyadi (WIM Solusi Prima, 2026)
Sustainability reporting has evolved into a critical mechanism for communicating environmental, social, and governance (ESG) performance and enhancing corporate transparency. However, the rapid expansion of sustainability disclosure practices has intensified concerns regarding greenwashing, where firms strategically misrepresent sustainability performance to create a favorable image. This study aims to systematically review and synthesize the literature on the interrelationship between sustainability reporting, greenwashing, transparency, and firm value. Using a systematic literature review approach, this study analyzes 62 peer-reviewed articles published between 2012 and 2025 from Scopus-indexed and high-quality scholarly sources. The findings reveal that sustainability reporting functions as a dual and context-dependent mechanism. On one hand, it reduces information asymmetry, improves disclosure quality, and enhances stakeholder decision-making, particularly in strong regulatory and governance environments. On the other hand, its inherent flexibility enables impression management, symbolic disclosure, and narrative manipulation, thereby facilitating greenwashing practices. The results further indicate that the impact of sustainability reporting on firm value is conditional upon disclosure credibility, where substantive and verifiable reporting contributes positively, while greenwashing leads to reputational damage, declining investor trust, and negative long-term valuation effects. The study also highlights the role of ESG rating divergence, weak standardization, and institutional heterogeneity in shaping disclosure credibility. This research contributes by integrating fragmented literature into a comprehensive framework and identifying greenwashing as a key moderating factor. Future research is encouraged to develop standardized greenwashing metrics and examine cross-country institutional differences.